Anorexia nervosa and childhood sexual abuse: Treatment outcomes of intensive enhanced cognitive behavioural therapy. (April 2018) - Calugi, Simona; Franchini, Cecilia; Pivari, Silvia; Conti, Maddalena; El Ghoch, Marwan; Dalle Grave, Riccardo
Abstract: Sexual abuse has been widely studied as a risk factor in anorexia nervosa, but data on its influence on treatment outcomes are scarce. Hence, we compared short- and long-term outcomes of inpatient enhanced cognitive-behavioural therapy (CBT-E) in patients with anorexia nervosa who had and had not suffered sexual abuse. Eighty-one patients were recruited, and body mass index (BMI), Eating Disorder Examination, Brief Symptom Inventory, and Work and Social Adjustment Scale scores were recorded before and after treatment, and at 6- and 12-month follow-ups. Twenty patients (24.7%) reported experiencing childhood sexual abuse before anorexia nervosa onset, while 61 (75.3%) reported none. Both groups displayed similar characteristics before treatment, and similarly large increases in BMI, eating-disorder, general psychopathology, and work and social functioning from baseline to 12-month follow-up. Based on these findings, childhood sexual abuse does not appear to compromise outcomes in patients with anorexia nervosa treated via intensive CBT-E. Highlights: Data on the influence of sexual abuse on treatment outcome in anorexia nervosa are scarce. 24.7% of patients with anorexia nervosa reported childhood sexual abuse. Patients treated with intensive CBT-E achieved a substantial increase in BMI. Patients had an improvement of eating disorder and general psychopathology. There was no difference in outcomes between patients with and without sexual abuse.